Starość pobłogosławiona przez Boga. Studium postaci w Łk 1–2 - Rosik, Mariusz (Verbum Vitae, 2013)
Whether God planned for people physical death and senility (are the death and senility a consequence of the original sin?) or not, is still an open question in modern theology. In the Infancy Narratives (Luke 1–2) the evangelist presents the four old persons: Zechariah, Elisabeth, Simeon, and Anne. Exegetical and theological examination of the texts concerning these individuals leads to some characteristics which are common for all or for most of them. Among them we can enumerate the following ones: remaining in God’s presence in Jerusalem temple, continuing to pray, being led and inspired by the Holy Spirit (prophecy included), expecting the coming of the Messiah and living according to the God’s Law (righteousness). It seems, however, that the most important characteristic of the old age is sensibility in recognizing God’s inspiration.